Effects of the EDF length and oscillation reflectivity on the output power of a 1.55 pm ring fiber laser system - Mohamad K. Abdullah,; P. Poopalan,; Mohd A. Mahdi,; Hanafi M. Said,; Mohd F. Assilam,; Harith B. Ahmad, (1998)
The effects of varying the Erbium doped fiber (EDF) length and the loop-back reflectivity of an all fiber ring laser system are presented. Two characteristics of the output power, namely the lasing threshold and the maximum power are analyzed. The reflectivity is taken as the percentage of the lasing signal that is fed (or reflected) back into the loop. The maximum output power refers to the power obtained at maximum pump power available, 115 mW. This therefore does not represent the actual maximum output power obtainable with the EDFL system which should be higher. For a particular system, there is an optimum length of EDF that gives the lowest lasing threshold. Smaller reflectivity is found to give a higher maximum output power but at the expense of a higher lasing threshold